Role of routine computed tomography scan in the oncological follow up of patients treated by radical cystectomy for bladder cancer. (15th July 2016) - Alimi, Quentin; Verhoest, Grégory; Kammerer‐Jacquet, Solene‐Florence; Mathieu, Romain; Rioux‐Leclercq, Nathalie; Manunta, Andréa; Laguerre, Brigitte; Guille, François; Bensalah, Karim; Peyronnet, Benoit
Abstract : Objectives: To assess the impact of a prolonged follow‐up schedule using computed tomography scan on oncological outcomes after radical cystectomy for bladder cancer. Methods: A single‐center retrospective study was carried out. All patients who underwent a radical cystectomy for bladder cancer between 1992 and 2012 were included. The protocol for postoperative oncological follow up included a thoracoabdominal computed tomography scan twice per year for 2 years and then annually for life. The patients with tumor recurrence were divided into two groups: asymptomatic recurrences and recurrences diagnosed because of symptoms. Cancer‐specific survivals were estimated using the Kaplan–Meier method and compared with the log–rank test. Cox proportional hazards regression models were used to determine the predictive factors of cancer‐specific survival. Results: Overall, 331 patients were included in this analysis, and, of them, 48.5% had a cancer recurrence after a median follow up of 52.6 months. A total of 30 of these recurrences were diagnosed at routine follow up among asymptomatic patients (18.8%). A total of 50% of recurrences occurred during the first 6 months and 75% during the first year. Just 10 of the recurrences (6.3%) appeared more than 3 years after radical cystectomy. The 5‐year cancer‐specific survival was higher in patients with asymptomatic recurrences (15.7% vs 32.1%), but this difference was not statistically significant ( P = 0.10). On multivariate analysis, detection of asymptomatic recurrence reached statistical significance (HR 0.55; P = 0.04). Conclusion: Routine computed tomography scan surveillance after radical cystectomy for bladder cancer might provide a survival benefit. The risk of recurrence beyond 3 years seems to be low, and further studies are required to determine the role of routine computed tomography scan in the follow up beyond this timeframe.